O-007 Treatment of pial arteriovenous malformations: single institution experience at Children's hospital boston. (16th November 2010) - Puri, A; Smith, E; Scott, M; Orbach, D
Abstract : Introduction: Pediatric cerebral arteriovenous malformations (AVMs) present an ongoing risk of hemorrhage compounded by long life expectancy. AVMs can be treated with microsurgery, embolization or radiosurgery, alone or in combination. We present a single center experience, over a 2.5 year period, in the management of pediatric pial AVMs. Methods: We retrospectively analyzed cases of pial AVMs, treated by a combination of preoperative embolization and/or surgical resection, performed by the senior authors (DBO, ERS and RMS) from November 2007 to March 2010. Dural fistulas and vein of Galen malformations were excluded. Clinical presentation, embolization and surgical approach, and outcomes were analyzed. 17 children with pial AVM were treated: nine males and eight females, ranging in age from 2 months to 16 years. Clinical presentation included intracranial hemorrhage in six patients, seizures in three, headaches in three, a combination of symptoms in three and incidental discovery in two. Ten patients underwent preoperative embolization for which exclusively Onyx was used. All embolized patients but one underwent resection following embolization (16/17) and were kept intubated with tight blood pressure parameters overnight, pending resection. All patients underwent catheter angiography immediately following resection, before reversing anesthesia, to document complete resection of the AVM. One patient underwent a combination of radiosurgery, embolization and resection of a complex, rapidly evolving AVM. Results: Embolization alone without resection was not attempted in any patient in this pediatric cohort. No clinical worsening was noted after embolization on the preoperative neurologic examination. Target embolization was achieved in all patients but one, in whom optimal microcatheter position could not be achieved. No residual AVM was seen in 14/16(88%) resected patients. Two of 16 (12%) patients had residual AVM nidus or early draining veins on postoperative angiograms and these patients immediately underwent further resection and a second postoperative angiogram; one of these two patients was again found to have residual AVM and was returned to the OR again for further resection, followed by postoperative angiography. One patient was found to have recurrence of AVM on 6 month follow-up angiography and was retreated with preoperative embolization followed by resection. One patient evidenced a dramatic increase in AVM volume between treatments and underwent three resections, two with preoperative embolization. 14/16 (88%) patients were discharged home, neurologically intact or unchanged. One patient (6%) had a visual field cut postoperatively, and another patient (6%) had postoperative hemiparesis, with onset of improvement within several days. One patient (6%), who had presented comatose after her initial hemorrhage, died in a long term care facility secondary to respiratory complications. Conclusions: Pediatric pial AVMs are dynamic entities which benefit from multidisciplinary treatment. An armamentarium of combined endovascular and open surgical treatment is safe and reliable. In particular, perioperative angiography provides high quality documentation of the completeness of AVM resection, allowing for immediate return to the OR, if necessary.